Preparation method and application of cellulose-based magnetic adsorption material

The continuous synthesis of magnetic Fe3O4/cellulose adsorption materials by in situ method has solved the problem that activated carbon adsorption materials cannot achieve ultra-low emissions of ammonia and amines and reduce adsorption performance after regeneration, and achieved good performance after efficient adsorption and material regeneration.

CN118384860BActive Publication Date: 2025-02-18QINGDAO MUNICIPAL HOSPITAL +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410417822.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2025-02-18
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

Existing activated carbon adsorption materials cannot achieve ultra-low emissions of ammonia and amines, and their adsorption performance is reduced after regeneration.

Method used

The magnetic Fe3O4/cellulose adsorption material was continuously synthesized by in situ method, and a mixed solution with a molar ratio of Fe(OH)3 and FeSO4 of 2:1 to 3, a cellulose solution and a sodium hydroxide solution were reacted under an inert gas atmosphere. Magnetic Fe3O4/cellulose adsorption material with high magnetic saturation strength was produced.

Benefits of technology

It achieves efficient adsorption of ammonia and amine, meets ultra-low emission requirements, and maintains good adsorption performance after regeneration of adsorbent materials, and is suitable for the purification of foul odor sources such as hospitals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004781355100000011
    Figure HDA0004781355100000011
  • Figure HDA0004781355100000012
    Figure HDA0004781355100000012
  • Figure HDA0004781355100000021
    Figure HDA0004781355100000021
Patent Text Reader

Abstract

The present invention relates to the field of gas purification technology, and in particular to a preparation method and application of a cellulose-based magnetic adsorption material. A magnetic Fe3O4 / cellulose adsorption material is continuously synthesized by an in-situ method, and the specific synthesis steps are as follows: (1) mixing Fe(OH)3 acetic acid solution and FeSO4 acetic acid solution; (2) dissolving cellulose in a solvent; (3) taking a sodium hydroxide solution; (4) mixing and reacting the liquids in step (1), step (2) and step (3) under an inert gas atmosphere to obtain a dark brown liquid; (5) centrifuging the dark brown liquid obtained in step (4) to obtain a precipitate, and the precipitate is dried and calcined to obtain a magnetic Fe3O4 / cellulose adsorption material with high magnetic saturation intensity. The present invention realizes the complete adsorption of ammonia or amines and meets ultra-low emissions; the adsorption material has excellent adsorption performance after regeneration, and finally realizes the efficient removal of ammonia / amine odors in public health places, and is particularly suitable for adsorption and purification of hospital odors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas purification, and in particular to a preparation method and application of a cellulose-based magnetic adsorption material. Background Art

[0002] Malodorous substances refer to all gaseous substances that stimulate the olfactory organs and cause people to feel uncomfortable and damage the living environment. The pollution sources that produce malodorous gases mainly include agricultural and animal husbandry odors, industrial odors, and urban public facilities odors. Among them, the odor of urban public facilities has the greatest impact on the social public environment and people's demand for high-quality air environment. In recent years, hospital odors as special public places have attracted more and more attention, such as medical odors, disinfectant odors, and hospital odors. Ammonia or amines are an important type of malodorous gases. When inhaled into the alveoli of the human body, they easily enter the blood through the alveoli, bind to hemoglobin, and destroy the oxygen transport function.

[0003] Adsorption is considered to be a simple and efficient method for treating malodor. Patent CN 104368307A discloses a method for preparing activated carbon for ammonia adsorption. The method uses commercial granular activated carbon as raw material, and is modified by impregnation with a metal inorganic salt solution to obtain an activated carbon material that efficiently adsorbs ammonia at room temperature. The modified metal in the activated carbon prepared by this method is prone to blockage of the activated carbon pore structure, resulting in poor ammonia removal effect. Patent CN 114682213A discloses a flame-retardant activated carbon modified by ionic liquid, which can effectively inhibit the oxidation heat release of activated carbon during the regeneration process and reduce the risk of fire caused by local overheating. However, so far, the biggest difficulty in the adsorption of ammonia by activated carbon is that the adsorption performance is reduced after the activated carbon is regenerated; in addition, it is difficult to achieve ultra-low ammonia emissions by activated carbon adsorption. Therefore, it is urgent to find an adsorption material that can replace activated carbon for the adsorption of ammonia and amines.

[0004] Patent CN 109092083A discloses a ferroferric oxide / regenerated cellulose material for dye wastewater treatment, wherein a magnetic Fe3O4 solid is first prepared by coprecipitation, then mixed with a cellulose solution to obtain a composite solution, and the composite solution is scraped, solidified, soaked and vacuum dried to obtain a Fe3O4 / regenerated cellulose forward osmosis membrane, wherein Fe3O4 / regenerated cellulose is intermittently synthesized by a two-step method, the synthesis process is complex, and continuous production of the material cannot be achieved, and it is not disclosed whether the material can be used to adsorb ammonia and amines. Patent CN 107362777A discloses a magnetic straw cellulose heavy metal ion adsorbent for heavy metal ion adsorption and separation, wherein a modified chemical precipitation method is used to prepare magnetic nanoparticles, and a series of methods are subsequently used to synthesize magnetic straw cellulose, but the problem of continuous synthesis is not essentially changed, and the saturation magnetization intensity of the synthesized material is only 10 to 30 mu / g.

[0005] Therefore, the prior art does not disclose that the magnetic Fe3O4 / cellulose adsorption material can adsorb ammonia and amines, and the preparation methods in the prior art all have certain problems. Summary of the invention

[0006] The present invention aims to solve the problem that activated carbon adsorption materials cannot achieve ultra-low emissions of ammonia and amines and the adsorption performance decreases after regeneration, and provides a cellulose-based magnetic adsorption material.

[0007] To achieve the above purpose, the present invention adopts the following technical solution:

[0008] A method for preparing a cellulose-based magnetic adsorption material, wherein the magnetic Fe3O4 / cellulose adsorption material is continuously synthesized by an in-situ method, and the specific synthesis steps are as follows:

[0009] (1) mixing Fe(OH)3 acetic acid solution and FeSO4 acetic acid solution;

[0010] (2) dissolving cellulose in a solvent;

[0011] (3) taking sodium hydroxide solution;

[0012] (4) mixing the liquids in step (1), step (2) and step (3) under an inert gas atmosphere and reacting to obtain a dark brown liquid;

[0013] (5) The dark brown liquid obtained in step (4) is centrifuged to obtain a precipitate, and the precipitate is dried and calcined to obtain a magnetic Fe3O4 / cellulose adsorption material with high magnetic saturation intensity. The magnetic saturation intensity of the adsorption material is 98mu / g, and the yield is more than 90%.

[0014] In step (1), the molar ratio of Fe(OH)3 to FeSO4 is 2:1-3.

[0015] The cellulose in step (2) is one of hydroxypropyl methylcellulose, ethyl cellulose or hydroxyethyl cellulose; and the solvent in step (2) is ethylene dichloride, methanol or water.

[0016] In step (4), the volume flow rate ratio of the mixed solution of Fe(OH)3 and FeSO4, the cellulose solution, and the sodium hydroxide solution is 6-9:16-25:30-45, and the preferred volume flow rate ratio is 8:20:40;

[0017] In step (4), the inert gas is one of N2, Ar or He.

[0018] The reaction temperature of step (4) is 160-190° C., preferably 180° C.; the reaction time is 5-30 min, preferably 10 min.

[0019] The precipitate in step (5) is dried at 100° C. for 5 h, and then calcined at 200-260° C. for 4 h to obtain a magnetic Fe3O4 / cellulose adsorption material with high magnetic saturation intensity.

[0020] A cellulose-based magnetic adsorption material prepared by the method.

[0021] The magnetic Fe3O4 / cellulose adsorption material is used for adsorbing ammonia, dimethylamine or trimethylamine.

[0022] The magnetic Fe3O4 / cellulose adsorbent material was prepared into 3-5 mm microspheres by spray drying.

[0023] The magnetic Fe3O4 / cellulose microspheres were arranged in an S-shaped manner in a microchannel reactor for adsorbing ammonia, dimethylamine or trimethylamine. The diameter of a single tube in the reactor was 7 mm. The concentration of ammonia, dimethylamine or trimethylamine was 10-5000 ppm and the space velocity was 15000 h -1 , the temperature is 40℃ or 60℃.

[0024] The microchannel reactor is a flat-plate structure, consisting of an air inlet system, an adsorption system and an air outlet system. The air inlet system is equipped with a plate-type gas distributor; the adsorption system is composed of multiple stainless steel tubes with a diameter of 7 mm arranged side by side, the inner wall of the tube has a silicon coating, and the magnetic Fe3O4 / cellulose microspheres are arranged in an S-shaped manner in the inner cavity of the stainless steel tube.

[0025] The present invention has the following advantages:

[0026] The method of the present invention continuously prepares the adsorption material through an in-situ method, and simultaneously introduces an Fe precursor, cellulose, and a NaOH solution into a material synthesis reactor, so that the magnetic Fe3O4 / cellulose has a higher magnetic saturation strength, and the adsorption strength of the adsorption material to ammonia or amines is improved; the magnetic Fe3O4 / cellulose microspheres are arranged in an S-shaped manner in a microchannel reactor to achieve complete adsorption of ammonia or amines and meet ultra-low emissions; the adsorption material has excellent adsorption performance after regeneration, and finally achieves efficient removal of ammonia / amine odors in public health places, and is particularly suitable for adsorption and purification of hospital odors. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The schematic diagram is a synthetic process for preparing cellulose-based magnetic adsorption materials according to the present invention.

[0028] Figure 2 Magnetic hysteresis regression lines of the magnetic adsorption materials prepared in Example 1, Example 2 and Example 3.

[0029] Figure 3 The present invention provides a microchannel reactor for adsorbing ammonia and amines.

[0030] Figure 4 These are the adsorption penetration curves of the cellulose-based magnetic adsorption materials of Examples 4-7 and Example 10 of the present invention.

[0031] Figure 5 These are the adsorption penetration curves of the cellulose-based magnetic adsorption materials of Examples 8 and 9 of the present invention.

[0032] Figure 6 These are the adsorption penetration curves of the cellulose-based magnetic adsorption materials of Examples 11 and 12 of the present invention.

[0033] Figure 7 These are the adsorption penetration curves of the materials of Examples 13, 14 and 15 after the cellulose-based magnetic adsorption materials of Examples 6, 10 and 7 of the present invention were regenerated. DETAILED DESCRIPTION

[0034] In order to more clearly illustrate the present invention, the following examples are given, but are not limited thereto.

[0035] Example 1

[0036] (1) Add 100 mL of 1 mol / L Fe(OH)3 acetic acid solution and 50 mL of 1 mol / L FeSO4 aqueous solution into beaker A respectively;

[0037] (2) Measure 500 mL of 10 g / L hydroxypropyl methylcellulose dichloroethane solution and add it to beaker B;

[0038] (3) Measure 500 mL of 1 mol / L sodium hydroxide solution and add it to beaker C;

[0039] (4) Figure 1 As shown, the liquids in beakers A, B, and C are added to a reaction tube with a heating furnace through a horizontal flow pump at a speed of 8 mL / min, 20 mL / min, and 40 mL / min, respectively. The time is 10 min, the switch on the device is turned on, and the operation is continued for 70 min. The temperature of the heating furnace is 180°C. At the same time, 100 mL / min of N2 is passed into the reaction tube through a mass flow meter, and the switch is turned off to finally obtain a dark brown liquid in a collecting bottle.

[0040] (5) The collected liquid was centrifuged to obtain a precipitate, which was dried at 100° C. for 5 h and calcined in a muffle furnace at 200° C. for 4 h to obtain magnetic Fe3O4 / cellulose with high magnetic saturation intensity, with a yield of 92%.

[0041] The magnetic hysteresis regression line is shown in Figure 2. The magnetic saturation intensity is 98emu / g, which is superparamagnetic.

[0042] Example 2

[0043] (1) Add 100 mL of 1 mol / L Fe(OH)3 acetic acid solution and 100 mL of 1 mol / L FeSO4 aqueous solution into beaker A respectively;

[0044] (2) Measure 500 mL of 10 g / L ethyl cellulose methanol solution and add it to beaker B;

[0045] (3) Measure 500 mL of 1 mol / L sodium hydroxide solution and add it to beaker C;

[0046] (4) The liquids in beakers A, B, and C were added to the reaction tube with a heating furnace through a horizontal flow pump at a rate of 9 mL / min, 16 mL / min, and 30 mL / min, respectively. The time was 30 min. The switch on the device was turned on and the operation was continued for 70 min. The temperature of the heating furnace was 160°C. At the same time, 100 mL / min of Ar was introduced into the reaction tube through a mass flow meter. The switch was turned off, and finally a dark brown liquid was obtained in a collection bottle.

[0047] (5) The collected liquid was centrifuged to obtain a precipitate, which was dried at 100° C. for 5 h and calcined in a muffle furnace at 240° C. for 4 h to obtain magnetic Fe3O4 / cellulose with high magnetic saturation intensity, with a yield of 93%.

[0048] The hysteresis regression line is shown in Figure 2. The magnetic saturation intensity is 76emu / g, which is superparamagnetic.

[0049] Example 3

[0050] (1) Add 100 mL of 1 mol / L Fe(OH)3 acetic acid solution and 150 mL of 1 mol / L FeSO4 aqueous solution into beaker A respectively;

[0051] (2) Measure 500 mL of 10 g / L hydroxyethyl cellulose aqueous solution and add it to beaker B;

[0052] (3) Measure 500 mL of 1 mol / L sodium hydroxide solution and add it to beaker C;

[0053] (4) The liquids in beakers A, B, and C were added to the reaction tube with a heating furnace through a horizontal flow pump at a rate of 6 mL / min, 25 mL / min, and 45 mL / min, respectively. The time was 5 min. The switch on the device was turned on and the operation continued for 70 min. The temperature of the heating furnace was 190°C. At the same time, 100 mL / min of He was introduced into the reaction tube through a mass flow meter. The switch was turned off, and finally a dark brown liquid was obtained in the collection bottle.

[0054] (5) The collected liquid was centrifuged to obtain a precipitate, which was dried at 100° C. for 5 h and calcined in a muffle furnace at 260° C. for 4 h to obtain magnetic Fe3O4 / cellulose with high magnetic saturation intensity, with a yield of 93%.

[0055] The hysteresis regression line is shown in Figure 2. The magnetic saturation intensity is 62emu / g, which is superparamagnetic.

[0056] Comparative Example 1

[0057] Fe3O4 / cellulose material was prepared by impregnation method. The specific operation was as follows: 0.0533mol Fe(OH)3 and 0.0266mol FeSO4 were dissolved in an appropriate amount of deionized water, and then 2g hydroxypropyl methylcellulose was added to the solution. The glass rod was continuously stirred to make the Fe species evenly dispersed on the cellulose surface. It was dried at room temperature overnight, and then further dried in an oven at 100℃ for 5h, transferred to a muffle furnace and calcined at 200℃ for 4h, and finally the Fe3O4 / cellulose material was obtained, with a yield of only 81%. The magnetic saturation intensity was 35emu / g.

[0058] Example 4

[0059] The magnetic Fe3O4 / cellulose adsorbent obtained in Example 1 was prepared into 3-5 mm microspheres by spray drying and arranged in an S-shaped manner in a microchannel reactor ( Figure 3 ). The adsorption purification process conditions of the magnetic adsorption material are: ammonia concentration 1000ppm, air velocity 15000h -1 , the temperature is 40℃. Figure 4 It can be seen that the time for maintaining 100% ammonia conversion is 790 minutes.

[0060] Example 5

[0061] The magnetic Fe3O4 / cellulose adsorbent obtained in Example 2 was prepared into 3-5 mm microspheres by spray drying and arranged in an S-shaped manner in a microchannel reactor ( Figure 3 ). The adsorption purification process conditions of the magnetic adsorption material are: ammonia concentration 1000ppm, air velocity 15000h -1 , the temperature is 60℃. Figure 4 It can be seen that the time for maintaining 100% ammonia conversion is 690 minutes.

[0062] Example 6

[0063] The magnetic Fe3O4 / cellulose adsorbent obtained in Example 3 was prepared into 3-5 mm microspheres by spray drying and arranged in an S-shaped manner in a microchannel reactor ( Figure 3The adsorption purification process conditions of the magnetic adsorption material are: ammonia concentration 1000ppm, air velocity 15000h -1 , the temperature is 40℃. Figure 4 It can be seen that the time for maintaining 100% ammonia conversion is 570 minutes.

[0064] Example 7

[0065] The adsorbent material obtained in Comparative Example 1 was prepared into microspheres of 3-5 mm by spray drying and arranged in an S-shaped manner in a microchannel reactor ( Figure 3 The adsorption purification process conditions of the magnetic adsorption material are: ammonia concentration 1000ppm, air velocity 15000h -1 , the temperature is 40℃. Figure 4 It can be seen that the time for maintaining 100% ammonia conversion rate is 330 minutes, which is significantly shorter than the time for maintaining 100% ammonia conversion rate in Examples 1-3.

[0066] Example 8

[0067] The magnetic Fe3O4 / cellulose adsorbent obtained in Example 1 was prepared into 3-5 mm microspheres by spray drying and arranged in an S-shaped manner in a microchannel reactor ( Figure 3 The adsorption purification process conditions of the magnetic adsorption material are: dimethylamine concentration 5000ppm, air velocity 15000h -1 , the temperature is 60℃. Figure 5 It can be seen that the time for maintaining 100% ammonia conversion is 610 minutes.

[0068] Example 9

[0069] The magnetic Fe3O4 / cellulose adsorbent obtained in Example 2 was prepared into 3-5 mm microspheres by spray drying and arranged in an S-shaped manner in a microchannel reactor ( Figure 3 The adsorption purification process conditions of the magnetic adsorption material are: trimethylamine concentration 5000ppm, air velocity 15000h -1 , the temperature is 40℃. Figure 5 It can be seen that the time for maintaining 100% ammonia conversion is 550 minutes.

[0070] Example 10

[0071] The magnetic Fe3O4 / cellulose adsorbent obtained in Example 3 was prepared into 3-5 mm microspheres by spray drying and arranged in an S-shaped manner in a microchannel reactor ( Figure 3 The adsorption purification process conditions of the magnetic adsorption material are: dimethylamine concentration 1000ppm, air velocity 15000h -1 , the temperature is 40℃. Figure 4It can be seen that the time for maintaining 100% ammonia conversion is 510 minutes.

[0072] Embodiment 11

[0073] The magnetic Fe3O4 / cellulose adsorbent obtained in Example 1 was prepared into 3-5 mm microspheres by spray drying and arranged in an S-shaped manner in a microchannel reactor ( Figure 3 The adsorption purification process conditions of the magnetic adsorption material are: ammonia concentration 10ppm, air velocity 15000h -1 , the temperature is 60℃. Figure 6 It can be seen that the time for maintaining 100% ammonia conversion is 1320 min.

[0074] Example 12

[0075] The magnetic Fe3O4 / cellulose adsorbent obtained in Example 2 was prepared into 3-5 mm microspheres by spray drying and arranged in an S-shaped manner in a microchannel reactor ( Figure 3 The adsorption purification process conditions of the magnetic adsorption material are: dimethylamine concentration 10ppm, air velocity 15000h -1 , the temperature is 40℃. Figure 6 It can be seen that the time for maintaining 100% ammonia conversion is 960 minutes.

[0076] Embodiment 13

[0077] The adsorption materials used in Example 6 were regenerated respectively. The specific operation was as follows: 150°C hot air was passed through the microchannel reactor through the gas inlet for 1 hour. Then the adsorption purification was continued. The process conditions were: ammonia concentration 1000ppm, space velocity 15000h -1 , the temperature is 40℃. Figure 7 It can be seen that the time for maintaining 100% ammonia conversion rate is 550 minutes, and the adsorption effect of the regenerated magnetic Fe3O4 / cellulose adsorption material has no obvious change compared with Example 6, indicating that the adsorption material still has a good adsorption effect after regeneration and can be reused.

[0078] Embodiment 14

[0079] The adsorption materials used in Example 10 were regenerated respectively, and the specific operation was as follows: 150°C hot air was passed through the microchannel reactor through the gas inlet, and the treatment time was 1 hour. Then the adsorption purification was continued, and the process conditions were: dimethylamine concentration 1000ppm, space velocity 15000h -1 , the temperature is 40℃. Figure 7It can be seen that the time for maintaining 100% ammonia conversion rate is 500 minutes, and the adsorption effect of the regenerated magnetic Fe3O4 / cellulose adsorption material has no obvious change compared with Example 10, indicating that the adsorption material still has a good adsorption effect after regeneration and can be reused.

[0080] Embodiment 15

[0081] The adsorption materials used in Example 7 were regenerated respectively. The specific operation was as follows: 150°C hot air was passed through the microchannel reactor through the gas inlet for 1 hour. Then the adsorption purification was continued. The process conditions were: ammonia concentration 1000ppm, space velocity 15000h -1 , the temperature is 40℃. Figure 7 It can be seen that the time for maintaining 100% ammonia conversion rate is 260 minutes, and the adsorption effect of the regenerated magnetic Fe3O4 / cellulose adsorption material is significantly reduced compared with Example 7, indicating that the adsorption effect of the adsorption material prepared in Comparative Example 1 becomes poor after regeneration and cannot be reused.

[0082] It can be seen from the above examples that the magnetic Fe3O4 / cellulose adsorption material of the present invention has a high magnetic saturation strength and has strong adsorption performance for ammonia, dimethylamine and trimethylamine. After the adsorption material is regenerated, it still has good adsorption performance and can be reused.

Claims

1. A method for preparing a cellulose-based magnetic adsorption material for adsorbing ammonia, dimethylamine or trimethylamine, characterized in that: The magnetic Fe3O4 / cellulose adsorption material was continuously synthesized by an in-situ method. The specific synthesis steps are as follows: (1) Mixing Fe(OH)3 acetic acid solution and FeSO4 acetic acid solution; (2) dissolving cellulose in a solvent; (3) Take sodium hydroxide solution; (4) mixing the liquids in step (1), step (2) and step (3) under an inert gas atmosphere and reacting to obtain a dark brown liquid; (5) centrifuging the dark brown liquid obtained in step (4) to obtain a precipitate, drying the precipitate at 100° C. for 5 h, and then calcining the precipitate at 200-260° C. for 4 h to obtain a magnetic Fe3O4 / cellulose adsorption material with high magnetic saturation strength; The cellulose in step (2) is one of hydroxypropyl methylcellulose, ethyl cellulose or hydroxyethyl cellulose; the solvent in step (2) is ethylene dichloride or methanol; The reaction temperature in step (4) is 160-190°C; In step (4), the volume flow rate ratio of the mixed solution of Fe(OH)3 and FeSO4, the cellulose solution, and the sodium hydroxide solution is 6-9:16-25:30-45.

2. The method for preparing the cellulose-based magnetic adsorption material according to claim 1, characterized in that: In step (1), the molar ratio of Fe(OH)3 to FeSO4 is 2:1-3.

3. The method for preparing the cellulose-based magnetic adsorption material according to claim 1, characterized in that: The reaction temperature of step (4) is 180°C and the reaction time is 5-30 min.

4. A cellulose-based magnetic adsorption material prepared by the method of claim 1.

5. An application of the cellulose-based magnetic adsorption material according to claim 4, characterized in that: The magnetic Fe3O4 / cellulose adsorption material is used for adsorbing ammonia, dimethylamine or trimethylamine.

6. The use according to claim 5, characterized in that: The magnetic Fe3O4 / cellulose adsorbent material was prepared into 3-5 mm microspheres by spray drying.

7. The use according to claim 6, characterized in that: The magnetic Fe3O4 / cellulose microspheres were arranged in an S-shaped manner in a microchannel reactor for adsorbing ammonia, dimethylamine or trimethylamine. The diameter of a single tube in the reactor was 7 mm. The concentration of ammonia, dimethylamine or trimethylamine was 10-5000 ppm and the space velocity was 15000 h -1 , the temperature is 40℃ or 60℃.

Citation Information

Patent Citations

  • Preparation method of special active carbon for ammonia adsorption

    CN104368307A

  • Preparation method of magnetic straw cellulose adsorbent for heavy metal ions

    CN107362777A

  • Preparation and application of ferroferric oxide / regenerated cellulose magnetic forward permeable membrane

    CN109092083A

  • Flame-retardant activated carbon for adsorbing ammonia gas and preparation method of flame-retardant activated carbon

    CN114682213A